Eksistensi Tarekat Junaidi Al-Baghdadi Terhadap Pembinaan Masyarakat Islam di Majelis Darul Ikhlas Kota Palangka Raya - Febrianti, Nadiya; Abubakar, Abubakar; Husni, Muhammad (Jurnal Studi Agama dan Masyarakat, 2019)
This study discusses the existence of the Junaidi Al-Baghdadi Tarekat in Palangka Raya. Its existence indicates the teaching of Islam named Darul Ikhlas. There are three main issues raised in this study: first, to find out the ins and outs of the Junaidi Al-Baghdadi tariqah. Second, how is the model of teaching, and third, how the existence of the Junaidi Al-Baghdadi tarekat so that it can survive. The purposes of this research are to find out the system of teaching and the existence of its development in Palangka Raya Town. The research method used is a historical approach in the form of qualitative field research studies with literature review techniques and data collection is done through observation, documentation, and interviews. The results showed that the development of the Junaidi Al-Baghdadi tariqa, in terms of quantity, one of which was the establishment of the Majlis Taklim Darul Ikhlas, which showed the development achieved with a simple guidance system. The contribution made by the Junaidi Al-Baghdadi Tarekat can be seen in terms of worship and social affairs. Thus, this Tarekat is facing progress and